2013
DOI: 10.1038/mt.2012.210
|View full text |Cite
|
Sign up to set email alerts
|

T Cells Redirected to EphA2 for the Immunotherapy of Glioblastoma

Abstract: Outcomes for patients with glioblastoma (GBM) remain poor despite aggressive multimodal therapy. Immunotherapy with genetically modified T cells expressing chimeric antigen receptors (CARs) targeting interleukin (IL)-13Rα2, epidermal growth factor receptor variant III (EGFRvIII), or human epidermal growth factor receptor 2 (HER2) has shown promise for the treatment of gliomas in preclinical models and in a clinical study (IL-13Rα2). However, targeting IL-13Rα2 and EGFRvIII is associated with the development of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
181
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 216 publications
(183 citation statements)
references
References 37 publications
2
181
0
Order By: Relevance
“…We and others have shown that experimental orthotopic GBM regresses after administration of HER2 or IL13Rα2 CAR T cells, yet tumors recur in 40%-60% of CAR T cell-treated animals (2)(3)(4)30). Therefore, we assessed the surface expression of HER2 and IL13Rα2 in a cohort of 3 primary GBM samples (unique patient numbers 1-3 [UPN 1-UPN 3]) obtained from surgical excision material (hereafter referred to as primary GBM).…”
Section: Antigen Escape Variants Prevail In Gbm Recurrences After Carmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have shown that experimental orthotopic GBM regresses after administration of HER2 or IL13Rα2 CAR T cells, yet tumors recur in 40%-60% of CAR T cell-treated animals (2)(3)(4)30). Therefore, we assessed the surface expression of HER2 and IL13Rα2 in a cohort of 3 primary GBM samples (unique patient numbers 1-3 [UPN 1-UPN 3]) obtained from surgical excision material (hereafter referred to as primary GBM).…”
Section: Antigen Escape Variants Prevail In Gbm Recurrences After Carmentioning
confidence: 99%
“…Adoptive transfer of chimeric antigen receptor-grafted (CARgrafted) (1) T cells has induced tumor regression in several preclinical models of glioblastoma (GBM) (2)(3)(4), osteosarcoma (5,6), and neuroblastoma (7). However, only sporadic clinical responses have been observed in early-phase clinical trials for these tumors (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…16), and ephrin type A receptor 2 (EphA2; ref. 17). In addition, CAR-transduced T cells can migrate through the microvascular walls and penetrate tumors (14,16).…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study by Chow et al T cells expressing CAR specific for EphA2 were able to attack and kill GBM cell lines in vitro and cause GBM tumor regression in mice [46]. EphA2 is a fairly novel antigen target and further studies are needed to elaborate on its significance in the treatment of GBM patients.…”
Section: Future Gbm Immunotherapy Antigens Epha2mentioning
confidence: 99%